Consequences on aging process and human wellness of generation of nitrogen and oxygen species during strenuous exercise. (2nd January 2020) - Sessa, Francesco; Messina, Giovanni; Russo, Raffaele; Salerno, Monica; Castruccio Castracani, Carlo; Distefano, Alfio; Li Volti, Giovanni; Calogero, Aldo E.; Cannarella, Rossella; Mongioi', Laura M.; Condorelli, Rosita A.; La Vignera, Sandro
Abstract: Impairment of antioxidant defense system and increase in metabolic rate and production of reactive oxygen species have been demonstrated in strenuous exercise. Both at rest and during contractile activity, skeletal muscle generates a very complex set of reactive nitrogen and oxygen species; the main generated are superoxide and nitric oxide. The nature of the contractile activity influences the pattern and the magnitude of this reactive oxygen and nitrogen species (ROS) generation. The intracellular pro-oxidant/antioxidant homeostasis undergoes alteration owing to strenuous exercise and the major identified sources of intracellular free radical generation during physical activity are the mitochondrial electron transport chain, polymorphoneutrophil, and xanthine oxidase. Reactive oxygen species increased tissue susceptibility to oxidative damage and pose a serious threat to the cellular antioxidant defense system. The possible dangerous consequences of the aging process and human wellness are emphasized in this review.